Canadian Identity and Canada’s Indian Residential School Apology - Stabler, Jason (eTopia, 2010)
Canada’s more than century-long Indian Residential Schools system transferred Indigenous children from their homes and communities to state- and church-run schools with the goal offacilitating their assimilation into Canadian society. In 2008, Canada delivered an official apology for its role in the system and its legacy. This apology has the potential to heal Indigenous/Settler-state relations, but to do so it must transform existing relationships and further simple coexistence as a reconciliation mechanism. The social construction of Canadian identity as lawful and benevolent may present a barrier in achieving these goals and may ultimately hinder meaningful reconciliation with Indigenous peoples.